Integrating Contextual Learning Model and Outcome-Based Education in EFL Classroom of Higher Education - Hardiah, Mei; Damayanti, Indah; Arono; Yunita, Wisma (International Journal of Innovation and Education Research, 2025)
Integrating CTL and OBE in teaching English as a foreign language is possible to apply in the university context since both approaches are based on a student-centered approach and focus on outcomes as authentic assessment. This research was conducted to find out the implementation of integrating CTL and OBE in the English Morphology class. The students of the 3rd semester acted as the subject of the research. The implementation of CTL in the teaching and learning process included the components of constructivism, inquiry, asking, learning community, reflection, and authentic assessment. The OBE result was based on students' projects, which were measured by observing students' knowledge and performance through presentation. The result revealed that integrating CTL and OBE in English Morphology class consequently eases the students to comprehend the concept of morphology as realized from the student project. It can be concluded that integrating CTL and OBE in teaching theoretical subjects in a higher education EFL context affects the students positively. Further research with different approaches to the research is suggested to be conducted. Keywords: CTL, OBE, Integrating, English Morphology Course